Macrohongos de Colombia II. Listado de especies de los órdenes Agaricales, Boletales, Cantharellales y Russulales (Agaricomycetes, Basidiomycota). (2010)
ABSTRACT: Interest in the study of macrofungi has increased in Colombia during the past 50 years. Mountain forests have been the sites better explored, from the mycological point of view, providing the largest number of genera and species. So far, the country’s literature reports 605 macrofungi species belonging to the Agaricales, Boletales, Cantharellales, and Russulales orders (Basidiomycota). This new list, which is a continuation of work carried out by Franco Molano and Uribe-Calle in the year 2000, includes 175 species, distributed into 73 genera: 151 belonging to Agaricales, 14 to Boletales, 9 to Russulales, and only one to Cantharellales. 31 species constitute new records for the country.